Development of additional autoimmune diseases in a population of patients with systemic lupus erythematosus - McDonagh, J (2000)
OBJECTIVE—In view of the recognised clustering of autoimmune diseases (AID), the chronology of development of other autoimmune diseases in systemic lupus erythematosus (SLE) patients was considered. METHODS—A retrospective review of a well documented population of 215 patients with SLE was undertaken. The duration of follow up ranged from 2 to 18( )years. RESULTS—Of these 215 patients, 65 (30%) had at least one other AID—including 51 (24%) having one other AID, 12 (6%) having two and two (1%) having three other AID in addition to their SLE. Twelve different autoimmune diseases were identified. The majority of patients developed a further AID after SLE had been diagnosed (62%) reflecting the relatively early age of onset of SLE. There was no significant difference in the age of onset of rheumatoid arthritis, Sjögren's syndrome and hypothyroidism that had developed before SLE compared with those who developed these diseases after SLE. However, those who developed autoimmune thrombocytopenia (AITP) before SLE were significantly younger than those who developed AITP after SLE (16.7 v 38.7 years respectively, p<0.05). CONCLUSIONS—Physicians caring for SLE patients should remain alert to the possible development of a second AID during follow up. Further well matched case-control studies are required to define the exact relation between SLE and other AID.